The Period of Development of Khorazm's Charitable Traditions - Sabirova Nasiba Ergashevna (International Journal on Orange Technologies, 2024)
This article discusses the latest developments in the art of giving. Also, the parikhan-porkhans scattered in Khorezm are a form of shamans, and shamanism is considered to be one of the first stages in the formation of the art of Bakhshi, and the professions of medicine and sorcery were synthesized in the Bakhshi, who were masters of music and words, even Ergash Jumanbulbul information was given that his son also performed the role of "goshkoch". In particular, in the article, it is emphasized that in the researches of ANSamoylovich, Khorezm Bakhshis narrated that they sang book epics, played dutor, bulamon. In Khorezm, the words shaman, ozan, bakhshi were used, and now the term bakhshi is widely popular. The deification of the person of Bakhshchik is related to their high memory and ability to speak. There are opinions that the singing of epics accompanied by drums by the owners of this profession is related to the 10th-11th centuries. This phenomenon may be much older. The basis for this can be the paintings in the "Room of the Harp Woman" in the ancient Khorezm fortresses. A historical person (1115-1191) who is considered to be the first Bakhshi and Piri of Bakhshis in Khorezm is Ashiq Aydin (Ashug'iddin Umar Suhravardi), who is still the patron of Bakhshis. His person is also deified. According to historical sources, Ashiq Aydin was a master of music and words and at the same time a statesman. A treatise on music is also finished. Considering that he lived during the reign of the Khorezmshahs, it is possible to understand that there was a developed period of Bakhshi art in those times. After Ashiq Aydin Pir, Korqut father is the son, shaman, bakshi who spread the word in the Turkic world. It has been mentioned that the XIX and early XX centuries were the most flourishing period of Khorezm baksheek art.